Pharmacokinetics of oxiracetam and its degraded substance (HOPAA) after oral and intravenous administration in rats - Xinhuan Wan; Xiaohong Liu; Zheng Liu; Panqin Ma; Feitong Zhang; Xiangrong Zhang; Jin Sun (Elsevier, 2014)
The pharmacokinetics of oxiracetam and its degraded substance (4-hydroxy-2-oxo-1-pyrrolidine acetic acid, HOPAA) after oral and intravenous administration in rats were studied using an established UPLC-MS/MS method. Three groups of rats after an overnight fasted received 10 g/kg (n = 6) oxiracetam suspensions orally, and 2 g/kg (n = 6) normal or degraded oxiracetam injections intravenously via a caudal tail vein, respectively. Before the pharmacokinetic experiment, a simple safety evaluation test was conducted on the degraded oxiracetam injections containing 16.16% HOPAA in mice. There was no mortality by a single intravenous dose of 2 g/kg of degraded oxiracetam injections within two weeks, demonstrating that HOPAA was non-toxic in mice. Following intravenous administration of the normal injections, the plasma concentration-time curves of oxiracetam and HOPAA both showed a rapid elimination phase. The values of t1/2 were 3.1 ± 1.5 h for oxiracetam and 0.8 ± 0.2 h for HOPAA, and the mean residence times (MRT) were 1.2 ± 0.1 h and 0.8 ± 0.1 h, respectively. Oxiracetam and HOPAA after intravenous administration of the degraded oxiracetam injections presented elimination patterns similar to those observed in the normal injections. Oral pharmacokinetic results showed that the Tmax was less than 1.5 h for the two analytes, and both had a longer t1/2 and MRT than those of intravenous administration. Contents of HOPAA in three groups were calculated based on AUC0-t values of the two analytes. The quantitative change of HOPAA in vivo was also evaluated by comparing the plasma concentrations of HOPAA and oxiracetam at the same time for every group. Additionally, the values of absolute bioavailability of oxiracetam were about 8.0% and 7.4% calculated by the normal or degraded oxiracetam injections, which were far less than the value of 75% reported in literature, indicating the necessity of further study.